Analysis of the functions of keywords assigned by authors in scientific publications in events and journals - Fujita, Mariangela Spotti Lopes [UNESP] (Univ Estadual Campinas - Sistema Bibliotecas, 2024)
Introduction: The author, with your prior knowledge of the subject of your article, can be considered a domain expert indexer when assigns keywords from your domain expert language that represent meaningful content in journal, event, and repository submission systems. Objective: The study on the indexing of the scientific author as an indexer had the objective of investigating the functions attributed to keywords in scientific publications from events and journals in two areas of knowledge, Information Science and Education. Methodology: Exploratory research was carried out with papers from the ENANCIB (Information Science) and ANPED (Education) events and articles from Qualis A1 and A2 journals in the SciELO Information Science and Education collection. Annotation method of functions of keywords was applied and category determination according to the context of the abstract and title. Results: The most frequent keywords are represented by the functions Research topic and Research object and the least frequent ones represented by the functions Data, Research area, Others and Research method. Conclusion: It is concluded that the two main functions are Research object and Research topic.
Keywords: Indexing; Knowledge representation